THE CHALLENGES OF POLYPHONY: A PERSPECTIVE ON NEW ZEALAND LOCAL GOVERNMENT - Barrett, Jonathan (The journal of contemporary issues in business and government, 2011)
In modern democracies, just governance is dependent on decision-makers hearing plural citizens’ voices. Recognition of multiple, conflicting, yet equally valid voices may be described as polyphony. New Zealand’s Local Government Act 2002 mandates participation by local residents in the decision-making processes of their councils. Drawing on research into two councils, which manifest distinctly different approaches to citizen participation, this article looks at the challenges for local government engagement with polyphony. First the position of speakers is considered, with focus on the conditions for and barriers to speech in a local community context. Second, consideration is given to the position of intermediaries, those who filter, amplify or otherwise modify others’ voices. Third, the position of decision-making hearers is considered. Finally, an outline is given of how two particular councils engage with the issues raised by polyphony.